Kekuatan Hukum Pelaksanaan Perjanjian Kerja Karyawan Magang Bakti Dengan Bank Central Asia Berdasarkan Undang-Undang Ketenagakerjaan - Inabela, Wellana Kusuma; , Shalman Al Farizi, S.H., M.Kn (2017)
Employment issues in Indonesia related to the employment relationship is not balanced between employers and workers in manufacturing employment agreement. Not only is not balanced in making treaties, but the climate of increasingly tough competition is causing companies to improve efficiency of production cost (cost of production). One solution is to Magang Bakti system, where this system can save your company in the financing of human resources (HR) is working in the company in question. Problems examined the research is: (1) how the legal basis apprentice Magang Bakti employed in scope Bank Central Asia in terms of the provision as regulated in legislation number 13 years 2003 ? (2) the extent to which legislation number 13 years 2003 about manpower provide legal protection to apprentice Magang Bakti employed in the Bank Central Asia.